Performance of Row Spacing on the Yield of Sesame Varieties (Bangladesh Agronomy Journal, 2023)
The experiment was carried out during kharif-I season of 2020 in the experimental field of Regional Agricultural Research Station (RARS), Bangladesh Agricultural Research Institute (BARI), Cumilla to evaluate the optimum plant spacing of sesame varieties. There were four plants spacing S1 (30 ××5 cm2), S2 (30×× 10 cm2), S3 (40 ××5 cm2) and S4 (40×× 10 cm2) and two sesame varieties of V1 (BARI Til 3) and V2 (BARI Til 4) were included in the experiment. The experiment was conducted using a split-plot design with three replications. The highest seed yield (1646 kg ha-1) was found from BARI Til 4 but the highest number of capsule plant-1 and number of branches plant-1 were obtained from BARI Til-3. The maximum seed yield (1913 kg ha-1) was achieved in the interaction of S4V2 (40 ××10 cm2 and BARI Til 4) that was identical to S2V2 (30 x 10 cm2 and BARI Til 4).Bangladesh Agron. J. 2023, 26(1): 28-31